Pathological and Molecular Studies of Neospora caninum Infection in Aborted Bovine Foetuses in Khorasan Razavi Province, Iran - Asma Keyvanlou Shahrestanaki; Hossein Nourani; Gholamreza Razmi (Veterinary Medicine and Science)
ABSTRACT Background Neospora caninum is an obligate intracellular protozoan that is well established as a causative agent of abortion in dairy cattle worldwide. Objectives The objective of this study was to determine the role of N. caninum infection in the abortion in dairy cattle in the Khorasan Razavi Province, Iran. Methods From 2022 to 2024, 105 aborted bovine foetuses were collected from dairy cattle in Khorasan Razavi province. Brain samples of aborted foetuses were tested using nested PCR and histopathological examination. In addition, blood samples were collected from dairy cattle that had aborted PCR‐positive foetuses and were analysed using enzyme‐linked immunosorbent assay (ELISA). Results and Conclusions In the present study, N. caninum infection was detected in 24.76% (26 out of 105) of aborted bovine foetuses by nested PCR analysis. The brain tissues of 20 bovine‐aborted foetuses were only suitable for histopathological examination. Lesions of the central nervous system were severe hyperaemia, perivascular cuffing, astrogliosis, mild encephalitis and focal necrosis. One foetus exhibited a 32‐µm N. caninum cyst within the brain tissue. IgG antibodies against N. caninum were identified in all dairy cattle that aborted infected foetuses through ELISA testing. Molecular, histopathological and serological findings strongly suggest that N. caninum plays a significant role in bovine abortion in dairy cattle in Khorasan Razavi Province, northeast Iran.